Diseño de un sistema de conservación para el cantón Arenillas - Cún Romero, Luis Miguel (2014)
This Conservation System for Arenillas canton aims to integrate the protected area that makes up the National System of Protected Areas (SNAP), with public and private entities with environmental affinity, in order to work on protection activities natural resources. It was determined that in the canton has an Ecological Reserve, Protected Forest and Socio forest area, the predominant vegetation type in the canton is the Deciduous Forest Coastal Lowlands with 24.72%, predominantly in the protected area shrub vegetation with 54.49%, two areas of conservation significance vegetation is natural and are not being protected, are continuous from the others and there are plenty of vegetation relative to the total area was determined, the representativeness of formations predominant plant is evergreen Lowland Forest Coast with 98.91%. Finally, arise the composition and structure of the cantonal Conservation System, which strengthens the Municipal Development plans and Zoning (PDOT), arises as a parish.